Reporting and Concordance of Methodologic Criteria Between Abstracts and Articles in Diagnostic Test Studies - Estrada, Carlos A.; Bloch, Richard M.; Antonacci, Diana; Basnight, Lorraine; Patel, Sangnya T.; Patel, Sanjay C.; Wiese, Wilhelmine (East Carolina University, 2000)
OBJECTIVE: To evaluate the quality and concordance of methodologic criteria in abstracts versus articles regarding the diagnosis of trichomoniasis. STUDY DESIGN: Survey of published literature. DATA SOURCES: Studies indexed in medline (1976–1998). STUDY SELECTION: Studies that used culture as the gold or reference standard. DATA EXTRACTION: Data from abstract and articles were independently abstracted using 4 methodologic criteria: (1) prospective evaluation of consecutive patients; (2) test results did not influence the decision to do gold standard; (3) independent and blind comparison with gold standard; and (4) broad spectrum of patients used. The total number of criteria met for each report was calculated to create a quality score (0–4). MEASUREMENTS AND MAIN RESULTS: None of the 33 abstracts or full articles reported all 4 criteria. Three criteria were reported in none of the abstracts and in 18% of articles (95% confidence interval [95% CI] 8.6% to 34%). Two criteria were reported in 18% of abstracts (95% CI, 8.6% to 34%) and 42% of articles (95% CI, 27% to 59%). One criterion was reported in 42% of abstracts (95% CI, 27% to 59%) and 27% of articles (95% CI, 15% to 44%). No criteria were reported in 13 (39%) of 33 abstracts (95% CI, 25% to 56%) and 4 (12%) of 33 articles (95% CI, 4.8% to 27%). The agreement of the criteria between the abstract and the article was poor (κ−0.09; 95% CI, −0.18 to 0) to moderate (κ 0.53; 95% CI, 0.22 to 0.83). CONCLUSIONS: Information on methods basic to study validity is often absent from both abstract and paper. The concordance of such criteria between the abstract and article needs to improve. Originally published Journal of General Internal Medicine, Vol. 15, No. 3, Mar 2000
Keywords: Evidence-based medicine; Periodicals; Publishing; Quality control; Sensitivity and specificity; Diagnosis